Composto de pó de tabaco como fonte de nitrogênio à produção de grãos e forragem - Bremm, Nestor (2021)
Tobacco activity is of paramount importance to Brazil, as it is the world's largest tobacco exporter. However, tobacco processing and processing in industries generate high amounts of highly toxic residues. In order to overcome this problem, this residue was converted into a compost that has potential for agricultural use. Thus, the objective was to evaluate the immediate (study I) and residual (study II) effects of the tobacco powder compost as a potential fertilizer for crops. Study I consisted of three experiments, which involved different crops (Sudan grass, corn and soybeans). In the experiments in which the grasses were used, two factors were tested, the doses (0%, 50%, 100% and 200% of the tobacco compound and an additional mineral treatment, NPK) and the mode of application (incorporated versus superficial ). In the soybean experiment, different doses of compost (0, 2, 4 and 8 Mg ha-1 of compost and an additional mineral treatment, PK) were tested. Surface application of the compost provided higher dry matter yield and nitrogen (N) accumulation in relation to soil incorporation. The higher the dose of compost applied, the greater the productivity and accumulation of N, regardless of the crop. Mineral fertilization presented yield and N accumulation similar to intermediate doses of compost, except for the N accumulation in soybean, which was similar to the control. Regarding the N efficiency indices, it was observed that mineral fertilization showed the highest efficiency, followed by the lowest dose of compost. Regarding study II, this consisted of an experiment of three crops in a row (oats, corn and oats), where two factors were tested, the doses (0%, 50%, 100% and 200% of the tobacco compound and one additional mineral treatment, NPK) and the area's application history (two versus one compost application). Tobacco powder compost showed a residual effect on dry matter and nitrogen accumulation in crops, where it was observed that two applications of compost had a more significant residual effect, compared to a single application. The higher the dose of tobacco dust compost applied to the soil, the greater the residual effect on DM production and N accumulation for oat and corn crops. The residual effect of mineral fertilization provided similar dry matter and N accumulation in crops similar to compost underdose (50%).